A folded π-system with supramolecularly oriented dipoles: single-component piezoelectric relaxor with NLO activity. Issue 10 (25th January 2023) - De, Soumi; Asthana, Deepak; Thirmal, Chinthakuntla; Keshri, Sudhir K.; Ghosh, Ram Krishna; Hundal, Geeta; Kumar, Raju; Singh, Satyendra; Chatterjee, Ratnamala; Mukhopadhyay, Pritam
Abstract : We have shown that organic folded structures can be utilized to elicit piezo-, ferroelectric and efficient second harmonic generation – all within a single component, macroscopically dipole active system. Abstract : Organic molecules with an active dipole moment have a natural propensity to align in an antiparallel fashion in the solid state, resulting in zero macroscopic polarization. This primary limitation makes the material unresponsive to switching with electric fields, mechanical forces, and to intense laser light. A single-component organic material that bestows macroscopic dipole-driven electro-mechanical and optical functions, e.g., piezoelectric, ferroelectric and nonlinear optical (NLO) activity, is unprecedented due to the design challenges imparted by crystal symmetry and dipole orientations. Herein we report a crystalline organic material that self-assembles with a polar order ( P 1 ), and is endowed with a high piezoelectric coefficient ( d 33 –47 pm V −1 ), as well as ferroelectric and Debye-type relaxor properties. In addition, it shows second harmonic generation (SHG) activity, which is more than five times that of the benchmark potassium dihydrogen phosphate. Piezoelectric force microscopy (PFM) images validated electro-mechanical deformations. Piezoresponse force spectroscopy (PFS) studies confirmed a signature butterfly-like amplitude and a phase loop. To the best of our knowledge, this is the first report of a folded supramolecular π-system that manifests unidirectionally oriented dipoles and exhibits piezoelectricity, ferroelectricity, and has excellent ability to generate second harmonic light. These findings can herald new design possibilities based on folded architectures to explore opto-, electro- and mechano-responsive multifaceted functions.